2016
DOI: 10.1556/030.63.2016.1.5
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Molecular and Phenotypic Methods for the Detection and Characterization of Carbapenem Resistant Enterobacteriaceae

Abstract: In recent years, there has been a rapid dissemination of carbapenem resistant Enterobacteriaceae (CRE). This study aimed to compare phenotypic and molecular methods for detection and characterization of CRE isolates at a large tertiary care hospital in Saudi Arabia. This study was carried out between January 2011 and November 2013 at the King Khalid University Hospital (KKUH) in Saudi Arabia. Determination of presence of extended-spectrum beta-lactamases (ESBL) and carbapenem resistance was in accordance with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 29 publications
2
13
0
Order By: Relevance
“…Among the ESBLs, CTX-M was the most common gene found (16.5%) both individually and in combination (22.3%), followed by TEM-type ESBLs (9.7%) individually and (15.5%) in association and SHV-type ESBLs (4.8%) individually and (1.9%) in association. PCR for MBLs showed bla NDM-1 and bla VIM (6.7%) to be the most dominant type found followed by bla IMP (3.8%) and bla SIM-1 (0.9%) gene similar to a study by Somily et al [34]. One E. coli strain was found to harbor SIM-1 gene and another E. coli strain, which was identified with high resistance to all the antibiotics except colistin was positive for bla CTX-M , bla TEM , bla NDM-1 , armA, and rmtB genes.…”
Section: Discussionsupporting
confidence: 87%
“…Among the ESBLs, CTX-M was the most common gene found (16.5%) both individually and in combination (22.3%), followed by TEM-type ESBLs (9.7%) individually and (15.5%) in association and SHV-type ESBLs (4.8%) individually and (1.9%) in association. PCR for MBLs showed bla NDM-1 and bla VIM (6.7%) to be the most dominant type found followed by bla IMP (3.8%) and bla SIM-1 (0.9%) gene similar to a study by Somily et al [34]. One E. coli strain was found to harbor SIM-1 gene and another E. coli strain, which was identified with high resistance to all the antibiotics except colistin was positive for bla CTX-M , bla TEM , bla NDM-1 , armA, and rmtB genes.…”
Section: Discussionsupporting
confidence: 87%
“…A recent study from Turkey tested 77 isolates of K. pneumoniae and found that 74 isolates (89.16%) produced OXA-48 carbapenemase, whereas nine isolates (10.84%) produced both OXA-48 and NDM-1 by both phenotypic tests included CarbaNP test and CIM test [29]. Genotypic characterization of ESBL and carbapenemase genes by the Check-MDR CT102 was fully in agreement with phenotypic testing in the detection of 8 MBL in study by Somily et al [30].…”
Section: Discussionsupporting
confidence: 61%
“…For the optimal detection of carbapenem-resistant microorganisms, molecular biological methods are recommended. However, in resource-limited settings, a combination of phenotypic tests can be applied in diagnostic labs [36].…”
Section: Discussionmentioning
confidence: 99%